Relationship Between Test Anxiety and Academic Performance of Secondary School Students in Mathematics - Odiri Onoshakpokaiye; Ebele Chinelo Okigbo (Department of Mathematics Education University of Muhammadiyah Malang, 2023)
The study looked into i) the relationship that exists between test anxiety and secondary school students’ academic performance in Mathematics. ii) Whether there is difference between the academic performances of students with high and low test anxiety levels in mathematics. Two research questions and two hypotheses guided the study. A correlation survey design was adopted. The study population consisted of 42,299 senior secondary two (SS2) students offering mathematics 2021/2022 in Delta State, Nigeria and 1,650 of those students were selected using a multistage sampling procedure. Mathematics Test Anxiety Questionnaire (MTAQ), which was validated by three experts, was used as the instrument for data collection which had Cronbach Alpha coefficient of 0.69. The students’ achievement scores in Mathematics in SS1 for 2021/2022 session represent their performance scores in the subject. Pearson product moment correlation was used to analyze the collected data. The study’s findings revealed there was a negative correlation and also majority of the students experienced high test anxiety. There was no significant connection between test anxiety and students’ academic performance in mathematics. Also, there was a significant difference between students with high and low anxiety, and their academic performance in mathematics. In light of the findings, it was recommended among other things, that mathematics teachers, school guidance counsellors should make a concerted effort to reduce the test anxiety of their students through proper teaching and conditioning and modeling the behavior of the students for better mathematics performance.